Human hepatocytes support the hypertrophic but not the hyperplastic response to the murine nongenotoxic hepatocarcinogen sodium phenobarbital in an in vivo study using a chimeric mouse with humanized liver - Yamada, Tomoya; Okuda, Yu; Kushida, Masahiko; Sumida, Kayo; Takeuchi, Hayato; Nagahori, Hirohisa; Fukuda, Takako; Lake, Brian G; Cohen, Samuel M; Kawamura, Satoshi (Toxicological sciences, 2014)
High doses of sodium phenobarbital (NaPB), a constitutive androstane receptor (CAR) activator, have been shown to produce hepatocellular tumors in rodents by a mitogenic mode of action (MOA) involving CAR activation. The effect of 1-week dietary treatment with NaPB on liver weight and histopathology, hepatic CYP2B enzyme activity and CYP2B/3A mRNA expression, replicative DNA synthesis and selected genes related to cell proliferation, and functional transcriptomic and metabolomic analyses was studied in male CD-1 mice, Wistar Hannover (WH) rats, and chimeric mice with human hepatocytes. The treatment of chimeric mice with 1000-1500-ppm NaPB resulted in plasma levels around 3-5-fold higher than those observed in human subjects given therapeutic doses of NaPB. NaPB produced dose-dependent increases in hepatic CYP2B activity and CYP2B/3A mRNA levels in all animal models. Integrated functional metabolomic and transcriptomic analyses demonstrated that the responses to NaPB in the human liver were clearly different from those in rodents. Although NaPB produced a dose-dependent increase in hepatocyte replicative DNA synthesis in CD-1 mice and WH rats, no increase in replicative DNA synthesis was observed in human hepatocyte-originated areas of chimeric mice. In addition, treatment with NaPB had no effect on Ki-67, PCNA, GADD45β, and MDM2 mRNA expression in chimeric mice, whereas significant increases were observed in CD-1 mice and/or WH rats. However, increases in hepatocyte replicative DNA synthesis were observed in chimeric mice both in vivo and in vitro after treatment epidermal growth factor. Thus, although NaPB could activate CAR in both rodent and human hepatocytes, NaPB did not increase replicative DNA synthesis in human hepatocytes of chimeric mice, whereas it was mitogenic to rat and mouse hepatocytes. As human hepatocytes are refractory to the mitogenic effects of NaPB, the MOA for NaPB-induced rodent liver tumor formation is thus not relevant for humans.